1995
DOI: 10.1128/aac.39.4.979
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2'-fluoro-5-methyl-beta-L-arabinofuranosyluracil as a novel antiviral agent for hepatitis B virus and Epstein-Barr virus

Abstract: A novel anti-hepatitis B virus (anti-HBV) agent, 2-fluoro-5-methyl-␤-L-arabinofuranosyluracil (L-FMAU), was synthesized and found to be a potent anti-HBV and anti-Epstein-Barr virus agent. Its in vitro potency was evaluated in 2.2.15 and H1 cells for anti-HBV and anti-Epstein-Barr virus activities, respectively. In vitro cytotoxicity in MT2, CEM, 2.2.15, and H1 cells was also assessed, and the results indicated high antiviral selectivities of L-FMAU in these cells.A number of nucleosides have been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
133
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(135 citation statements)
references
References 25 publications
2
133
0
Order By: Relevance
“…4,5 Moreover, it has no effect on mitochondrial structure, or DNA content or function. 6,7 In woodchucks infected with woodchuck hepatitis virus (WHV), clevudine led to a decrease in the plasma WHV DNA of up to a thousand-fold.…”
Section: Nfection With Hepatitis B Virus (Hbv) Is Commonmentioning
confidence: 99%
“…4,5 Moreover, it has no effect on mitochondrial structure, or DNA content or function. 6,7 In woodchucks infected with woodchuck hepatitis virus (WHV), clevudine led to a decrease in the plasma WHV DNA of up to a thousand-fold.…”
Section: Nfection With Hepatitis B Virus (Hbv) Is Commonmentioning
confidence: 99%
“…Clevudine [1-(2-deoxy-2-fluoro-␤-arabinofuranosyl)thymine, L-FMAU] (CLV) is a pyrimidine analog with potent antiviral activity against HBV (4). CLV inhibits the DNA-dependent DNA activity of HBV polymerase, as well as reverse transcription and priming (1,16).…”
mentioning
confidence: 99%
“…Because of the broad spectrum of biological activities of 2'-F-arabinofuranosyl nucleoside, a number of structural modifications of these analogues have been carried out. Chu and coworkers have demonstrated that the enantiomer of FMAU, L-FMAU (2) is a promising agent against HBV [5] . It showed low toxicity in rates and woodchucks, potent in vivo antiviral activity against chronically infected woodchucks (WHV), respectable bioavailability and showed no significant virus rebound up to 36 weeks after cessation of the drug treatment.…”
Section: Introductionmentioning
confidence: 99%